SOSIALISASI MENGGUNAKAN INTERNET SECARA PANDAI BAGI REMAJA GRAHA CIANTRA INDAH - Pras Seprianto; Sri Nuryati; Elma Yulius (Universitas Islam 45 Bekasi, 2022)
Real Work Lecture (KKN) is one form of intracurricular which is the implementation of the Tri Dharma of Higher Education with the method of introducing and providing work experience and student learning in community empowerment. At Graha Ciantra Indah, especially on Rt 02 where I live, many people who attend junior high school use cellphones and use internet access, from this there are concerns from parents and the head of RT 02 about the habits of teenagers using cellphones and the internet. Therefore, I need to promote intelligent use of the internet, by presenting healthy internet material which contains about how to use internet access properly, ethical material on social media is related material when internet users interact with good social media, and internet crime material is a material about the types of internet crimes and ways to prevent internet users from committing internet crimes. This activity uses the Community Education method which is an extension activity that aims to increase understanding. With this activity, the results obtained during the activity, participants can understand the material and are able to answer questions from related speakers using the internet intelligently.